1972
DOI: 10.1139/b72-095
|View full text |Cite
|
Sign up to set email alerts
|

Variations and correlations within and between morphology, pathogenicity, and pectolytic enzyme activity in Sclerotinia from Saskatchewan

Abstract: One hundred and fourteen isolates of Sclerotinia from 23 different hosts in many parts of Saskatchewan were grouped, according to their morphology, on minimal medium. Two types of seedling pathogenicity tests on six host species were conducted on at least one isolate from each morphological group and one from each host species. A total of 38 isolates was tested. Assays for pectolytic enzyme activities of the same 38 isolates were done using a defined medium, and Swede turnip and carrot tissue as substrates. Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
0

Year Published

1980
1980
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(26 citation statements)
references
References 9 publications
6
20
0
Order By: Relevance
“…However, similar differences among S. sclerotiorum isolates have been reported by other workers even where a larger number of isolates were investigated (e.g., Riddle et al 1991;Ekins et al 2007;Morrall et al 1972). While variations in pathogenicity have been reported among isolates, the differences did not justify grouping of S. sclerotiorum isolates on the basis of their pathogenicity.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…However, similar differences among S. sclerotiorum isolates have been reported by other workers even where a larger number of isolates were investigated (e.g., Riddle et al 1991;Ekins et al 2007;Morrall et al 1972). While variations in pathogenicity have been reported among isolates, the differences did not justify grouping of S. sclerotiorum isolates on the basis of their pathogenicity.…”
Section: Discussionsupporting
confidence: 70%
“…While variations in pathogenicity have been reported among isolates, the differences did not justify grouping of S. sclerotiorum isolates on the basis of their pathogenicity. This is further supported by the observations of Melzer and Boland (1996) working on lettuce and Morrall et al (1972) on 23 different hosts, who defined a 'continuum' (in contrast to distinct categories) in the pathogenicity of this pathogen. Even where significant differences in pathogenicity among isolates of this pathogen occur, their responses were found to be overlapping (e.g., Riddle et al 1991;Ekins et al 2007).…”
Section: Discussionmentioning
confidence: 53%
See 1 more Smart Citation
“…Errampalli and Kohn (1995) did not find any correlation between pectic zymograms and 15 MCGs and Kull et al (2001) and Ekins (1999) observed that MCGs did not vary in aggressiveness. Even isolates that had been single-ascospore cultures from the same sclerotium were quite different with respect to their morphological, physiological and pathological characteristics (Morrall et al 1972). Furthermore, considerable variation in cultural morphology and aggressiveness was observed among protoplast-regenerated isolates of S. sclerotiorum, as compared with the isolates from different sources (Boland and Smith 1991).…”
Section: Discussionmentioning
confidence: 99%
“…Also, at least part of the resistance to S. sclerotiorum infection among lines of the scarlet runner bean (Phaseolus coccineus) could be attributed to differences in oxalate sensitivity (Chipps et al, 2005). Nonetheless, variation in these factors does not appear to be the primary determinant of pathogenicity as correlations have not always been apparent (Morrall et al, 1972). As an example, in S. trifoliorum, a degenerative non-virulent isolate of the pathogen produces more proto-pectinases than a normal string, but only the normal isolate secretes a toxin and is considered virulent (Held, 1955).…”
Section: Multiple Genetic Changes Associated With Gain Of Virulencementioning
confidence: 99%